2021
DOI: 10.1186/s13054-021-03687-2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of the lung injury of drowning: a systematic review

Abstract: Background Drowning is a cause of significant global mortality. The mechanism of injury involves inhalation of water, lung injury and hypoxia. This systematic review addressed the following question: In drowning patients with lung injury, what is the evidence from primary studies regarding treatment strategies and subsequent patient outcomes? Methods The search strategy utilised PRISMA guidelines. Databases searched were MEDLINE, EMBASE, CINAHL, We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 68 publications
(232 reference statements)
0
18
0
2
Order By: Relevance
“… 10 In recent years, several extensive literature reviews have been published on the treatment of drowning, including systematic and scoping reviews. 4 , 11 Thom et al reported that the use of ECMO is uncommon for drowning, and that there is a lack of evidence informing its use and efficacy in the management of drowning patients. 11 Therefore, it is crucial to record cases of ECMO for drowning, such as this present case, to build high‐quality evidence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 10 In recent years, several extensive literature reviews have been published on the treatment of drowning, including systematic and scoping reviews. 4 , 11 Thom et al reported that the use of ECMO is uncommon for drowning, and that there is a lack of evidence informing its use and efficacy in the management of drowning patients. 11 Therefore, it is crucial to record cases of ECMO for drowning, such as this present case, to build high‐quality evidence.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 11 Thom et al reported that the use of ECMO is uncommon for drowning, and that there is a lack of evidence informing its use and efficacy in the management of drowning patients. 11 Therefore, it is crucial to record cases of ECMO for drowning, such as this present case, to build high‐quality evidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we observed a higher proportion of patients developing ARDS in freshwater patients that could be related to the duration of immersion and the higher proportion of drowning-related cardiac arrest in these patients. Moreover, a recent review on pulmonary lesions induced by drowning highlighted the lack of evidence regarding the treatment of drowning associated ARDS [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, beyond early airway injury and cerebral hypoxia, infectious complications can have a profound influence on the clinical outcome. Late deaths from fungal Central Nervous System (CNS) complications have also been described, underlining the need for early fungal investigations and treatment 2,6 A recent review paper regarding near‐drowning intensive care 7 could not demonstrate a significant advantage when using prophylactic antibiotics in near‐drowning patients and highly contaminated submersion water. However, for dirty‐drowned children, both antibiotic and antimycotic prophylaxis appear mandatory.…”
Section: Figurementioning
confidence: 99%